"Focused introspection" during naturally increased diuresis: Description and repeatability of a method to study bladder sensation non‐invasively. Issue 5 (21st June 2013) - De Wachter, Stefan G G; Heeringa, Rhea; Van Koeveringe, Gommert A; Winkens, Bjorn; Van Kerrebroeck, Philip E V; Gillespie, James I
SUMMARY Objective To present and describe a non‐invasive method to study the origin and development of bladder filling sensation and to evaluate the repeatability of the method. Method Eighteen volunteers participated in the study and were given a water loading protocol consisting of 1, 000 ml water intake 1 hr before the session and 200 ml every 10 min during the session. Protocol 1: To evaluate diuresis rate, seven participants were asked to void every 15 min and the voided volume was measured. Protocol 2: Eleven volunteers graded bladder sensation on regular time points, on an empty graph with time on the X‐axis and intensity of sensation on the Y‐axis. The protocol ended at absolute need to void (maximal intensity) and voided volumes were measured. This protocol was conducted three times with a 10 days interval. Results Protocol 1: The diuresis rate was not different during the sessions and showed no variation over the studied time period (P = 0.2). Protocol 2: For an individual, the diuresis rate was not different between the sessions. The curves in all patients showed a continuously increasing bladder intensity. In seven participants the curve was convex, in the other four, the curve was sigmoidal. For each individual the pattern was constant during the three sessions. Conclusion A strict water loading protocol induces a constant diuresis. This allows individuals to draw an introspection bladder sensation curve with a specific shape, which can be used as a method to study the development of bladder sensation non‐invasively. Neurourol. Urodynam. 33:502–506, 2014. © 2013 Wiley Periodicals, Inc.